Strategi Adaptasi UMKM Kuliner Pada Masa Pandemi Covid-19 (Studi Kasus: Rumah Makan Haji Masduki, Pekalongan) - Risda Arofahtiani; Eko Ruddy Cahyadi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The Covid-19 pandemic has forced culinary business to adapt their strategies in order to keep continuous operation. Haji Masduki Restaurant is one example of the MSMEs that are much impacted by the pandemic and struggle to be survive. This study aims to formulate an adaptation strategy for the Haji Masduki Restaurant during the Covid-19 pandemic. Adaptation strategies can be implemented by Rumah Makan Haji Masduki by identifying strengths, weaknesses, opportunities and threats to be able to maintain and develop a business in the pandemic. The method used in this study is an analysis of the internal environment and the external environment, then an alternative strategy is made using a SWOT analysis and the best strategy is selected using the Analythical Hierarchy Process (AHP). The results of this study are the adaptation strategy with the highest score is to maintain and improve product and service innovation with an AHP method. Thus, Haji Masduki Restaurant can focus on increasing product innovation and restaurant services. Keywords: adaptation strategy, AHP, covid-19 pandemic, MSME, SWOT analysis